النظرية النسوية في التنمية - بحري, دلال (revue mofakir, 2018)
The concept of development in the old depends on how profit and interest only is the production, however, has witnessed in the recent period turnovers led to increased attention to the human being as an active ingredient in the creation of developmental processes, and this has coming of the theory of trying to put the human race is made up of women and men in one niche, as supports the role of women to participate in and manage the affairs of the society and this has emerged a new role for women Feminist theory has sought to find the status of women in the various branches, was the role of the views in their decision-making as successful women in managerial positions prestigious tradition